Country Independence Of State-Owned Enterprises: Relationship Between Private Law And Public Law - Arifardhani, Yoyo (Veteran Law Review, 2018)
BUMN is a business entity that all or part of its capital is owned by the state through direct participation from separated state assets. Based on its duties and responsibilities, BUMN has an important role in helping the government carry out the tasks of national economic development. This independence and professionalism are interpreted as free political interference in the operations of state-owned enterprises that can prevent BUMN from carrying out its duties and functions. The realization of the professionalism of this BUMN is challenged by two aspects, namely at the level of law and economic politics. The legal position of BUMN today is inseparable from the concept of state finances. The concept of state losses can be found in the State Finance Law and in more detail regulated in the State Treasury Law. Article 35 of the State Finance Law.